WORKLOAD AND JOB SATISFACTION ANALYSIS AS THE BASIS OF WORK SYSTEM IMPROVEMENT - Wahyudi, Roy; Zuraida, Rida; Pangestu, Felicia (Bina Nusantara University, 2018)
Employees’ workload can be high when the existing manpower is limited and the list of jobs to do are long. For the employee, the workload may affect their job satisfaction and their performance in the long-term. Assessment of workload and its influence to job satisfaction was done at Sustainability and Operation Department of cultivates and harvests oil palms Company in Indonesia. The workload was measured using NASA-TLX that measure mental demand, physical demand, temporal demand, performance, effort, and frustration. While job satisfaction is measured using a questionnaire about superiors’ support, colleagues assistance, remuneration, and promotion. The assessment result showed that employee’s workload in these departments was identified as rather high. This is coming from commonly overtime exists and high domestic traveling frequency. Besides that, there is a correlation between workload and job satisfaction. There is two correlations model, positive and negative. The high workload can improve the job satisfaction, but otherwise, it can decrease job satisfaction. To reduce the workload, information system and database suggested for the company to reduce the employee difficulty in accessing data to finish their job that caused excessive overtime.